Causal Relationship of Coronary Artery Calcium on Myocardial Infarction and Preventive Effect of Antiplatelet Therapy - Limpijankit, Thosaphol; Jongjirasiri, Sutipong; Unwanatham, Nattawut; Rattanasiri, Sasivimol; Thakkinstian, Ammarin; Laothamatas, Jiraporn (Frontiers in Cardiovascular Medicine, 2022)
Background: The role of coronary artery calcium score (CACS) to guide antiplatelet therapy in order to prevent myocardial infarction (MI) is still uncertain. This study aimed to find the causal relationship of CACS on MI and preventive effect of antiplatelet therapy. Methods: From 2005 to 2013, all patients with cardiovascular risk factors or symptoms of suspected CAD underwent coronary computed tomography. CACSs were measured using Agatston method and stratified into 4 groups: 0, 1 to 99, 100 to 399 and >400. Antiplatelet therapy was prescribed following physician discretion. Outcomes of interest were MI and bleeding. A mediation analysis was applied to find association pathways. CACS was considered as an independent variable, whereas antiplatelet therapy was considered as a mediator and MI considered the outcome of interest. Results: A total of 7,849 subjects were enrolled. During an average of 9.9±2.4 years follow-up, MI and bleeding events occurred in 2.24% (n=176) and 2.82% (n=221) of subjects, respectively. CACSs 100 to 399 and CAC >400 were significantly associated with the development of MI [OR 3.14 (1.72, 5.72), and OR 3.22 (1.66, 6.25), respectively, p<0.001]. Antiplatelet therapy reduced the risk of MI of these corresponding CAC groups with ORs of 0.60 (0.41, 0.78) and 0.56 (0.34, 0.77), p<0.001]. A risk of bleeding was associated with antiplatelet therapy (only aspirin), anticoagulant, hypertension, male gender and old age. Conclusion: CACS was associated with the development of future MI. The preventive effect of antiplatelet therapy was clearly demonstrated in subjects with CACSs equal to or above 100, but this benefit was partially offset by an increased risk of bleeding.